Donkey ploughs improve farm incomes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Ploughs designed for donkeys are helping Sudanese farmers to increase food production. The ploughs are also giving women farmers, who head some of the poorest households, the chance to improve family food security. Traditionally Sudanese farmers...